Higher‐Order Turbulence Statistics in the Earth's Magnetosheath and the Solar Wind Using Magnetospheric Multiscale Observations. Issue 12 (27th December 2018) - Chhiber, R.; Chasapis, A.; Bandyopadhyay, R.; Parashar, T. N.; Matthaeus, W. H.; Maruca, B. A.; Moore, T. E.; Burch, J. L.; Torbert, R. B.; Russell, C. T.; Le Contel, O.; Argall, M. R.; et al.
Abstract: High‐resolution multispacecraft magnetic field measurements from the Magnetospheric Multiscale mission's flux‐gate magnetometer are employed to examine statistical properties of plasma turbulence in the terrestrial magnetosheath and in the solar wind. Quantities examined include wave number spectra; structure functions of order two, four, and six; probability density functions of increments; and scale‐dependent kurtoses of the magnetic field. We evaluate the Taylor frozen‐in approximation by comparing single‐spacecraft time series analysis with direct multispacecraft measurements, including evidence based on comparison of probability distribution functions. The statistics studied span spatial scales from the inertial range down to proton and electron scales. We find agreement of spectral estimates using three different methods, and evidence of intermittent turbulence in both magnetosheath and solar wind; however, evidence for subproton‐scale coherent structures, seen in the magnetosheath, is not found in the solar wind. Plain Language Summary: The unique measurement capabilities of the Magnetospheric Multiscale mission are employed to investigate turbulence in the terrestrial magnetosheath and in the solar wind. These statistical analyses extend our knowledge of the turbulent environment in these near‐Earth space plasmas. Key Points: Structure functions up to 6th order are computed in magnetosheath and solar wind; differences are noted in the statistics in the two cases Agreement between single‐ and two‐spacecraft results confirms Taylor "frozen‐in" hypothesis at subproton scales Strong subproton‐scale intermittency is obtained for magnetosheath, but not for solar wind